Potencial fisiológico e sanidade de sementes de soja-hortaliça produzidas em diferentes adubações e armazenadas por doze meses - Lima, Juliana Maria Espíndola (2012)
Soybean seeds are of great importance for humanity, because of the abundant applicability of their products, cultivation easeness and for being the only plant protein most similar to animal products. The objective of this study was to determine the physiological potential and seed sanity of vegetable soybean produced in cerrado environment of Roraima with different fertilization and stored for 12 months. The experimental design was randomized blocks in a 5 x 2 factorial arrangement with five fertilization (conventional, intermediate, alternative, use of cassava waste water and carbonized rice hulls) and two seed evaluation periods (after harvest and after 12 months of storage). Two vegetable soybean (BRS 258 and BR 9452273) were assessed. Seeds were evaluated in laboratory concerning sanity, physical and physiological tests. Conventional, intermediate, alternative, with cassava waste water and carbonized rice hulls fertilizations, used at vegetable soybean cv. BRS 258 production, did not influence physiological seed quality after harvest but after 12 months of storage cassava waste water and carbonized rice hulls fertilizations are superior. Lineage BR 9452273 vegetable soybean seeds produced with five fertilization showed better physiological quality with cassava waste water fertilization. At harvest, incidence of fungi and bacteria do not reduce physiological quality of cv. BRS 258 and lineage BR 9452773 vegetable soybean seeds, produced with five different fertilizations. It found the Presence of Macrophomina phaseolina and Botryodiplodia theobromae was found among seeds of these two soybean genotypes, although there are no records relating to such fungi for this culture. Physiological quality of vegetable soybean seeds of the two genotypes studied is not preserved after 12 months storage in polyethylene terephthalate bottles. There was a decrease in physiological quality of cv. BRS 258 and lineage BR 9452273 vegetable soybean seeds after 12 months of storage, independently of fertilization used.